INCREASED INTENTION TO USE THE APPLICATION THROUGH BRAND TRUST AND QUALITY OF SERVICE (Research Study on Users of the Dana E-Money Application) - Salwa, Sekar; Hidayah, Riski Taufik; Maulida, Alya; Putri, Agfanita; Permana, Nurul Suryaningtyas; Larasati, Maudy (CENTRAL ASIA AND THE CAUCASUS, 2022)
In the face of increasing business challenges, especially in the digital business, trust in a brand is the most important capital in building good brand performance. One of the e-wallet businesses that is currently trending in Indonesia is Dana which is an online transaction application. However, in recent times, the fund application has experienced a decrease in users due to many complaints. This study was proposed toexamine the effect of service quality and brand trust on the intention to use the e-Money Dana application. This type of research is quantitative research using explanatory method by using purposive sampling technique to determine the criteria for sampling. In addition, a survey method was used in this study to obtain primary data in the form of direct responses from respondents. The sample selected in this study were 200 respondents who were among fund application users in Bandung. Based on the test results, the coefficient of determination for the brand trust variable is 41.34%, while the coefficient of determination for the service quality variable is 77.08. This shows that the two variables have a strong relationship, especially on the service quality variable. The limitation of this research is that the respondents are limited only in the city of Bandung. This study provides several recommendations,namely; (1) companies must pay attention to the speed in responding to complaints from consumers through the addition of customer service so that they can respond to consumer complaints quickly. (2) Companies must provide continuous information about the latest services so that consumers do not seek information from other e- commerce via social media.